The Role of Gut Microbiome in Initiation of Inflammatory Bowel Disease; A Review - Taher Azimi; Hossein Dabiri; Sahar Sabour; Aref Shariati; Javad Yasbolaghi; Hossein Dabiri (Fasa University of Medical Sciences, 2020)
Inflammatory bowel disease (IBD) is a prolonged and disabling functional gastrointestinal disorder with the incidence rate of more than 0.5% in public individuals, worldwide. IBD including Ulcerative colitis (UC) and Crohn's disease (CD) need to be taken into account that it is a heterogeneous illness which can take place by the convergence of host immune system disorders, genetic and environmental factors, gut microbiota dysbiosis, and can progress in people who are genetically susceptible. Overexposure of immune system to the excessive bacterial substances can also lead to the loss of immunological tolerance to bacteria, which are considered as normal flora in the body of the host which may subsequently result in bowel inflammation and IBD development. Generally, the role of infections in the initiation and development of inflammatory disease of the gastrointestinal tract has been studied by many clinical findings and it has been proved that gut microbiome via several mechanisms plays a significant role in initiation and exacerbation of IBD. It appears that the most important pathogens which correspond with the IBD include Helicobacter pylori, Clostridium difficile, Escherichia coli, Listeria monocytogenes, Campylobacter concisus as well as viruses such as Cytomegalovirus, Epstein Barr and Rubella. Based on the current knowledge, the current study discusses the most common pathogens that may be involved in the development of IBD and performs a comprehensive review on related evidence supporting or ignoring the possible role of microorganisms.